Pengembangan Pembelajaran Tendangan Dollyo Chagi Taekwondo pada Mata Pelajaran PJOK untuk Siswa SMA di Kecamatan Jayaloka Musi Rawas - Muhsana El Cintami Lanos; Joko Purnomo; Jujur Gunawan Manullang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
Learning the Dollyo Chagi kicking technique in Physical Education, Sports, and Health (PJOK) still faces challenges, including limited learning variations and students’ difficulties in mastering movement coordination, balance, and kicking accuracy. This study aimed to develop a Dollyo Chagi Taekwondo learning model for senior high school students in Jayaloka District, Musi Rawas Regency. The study employed a Research and Development (R&D) approach using the 4D development model, limited to the Define, Design, and Develop stages. The results produced six feasible learning models, namely Balloon Shadow, Bottle Bowling, Bottle Target Shooting, Balloon and Bottle Relay, Catch the Balloon, and Three-Station Circuit. Expert validation yielded an average score of 92.83% (highly valid), while the small-group and large-group practicality tests achieved average scores of 91.06% and 93.36%, respectively (highly practical). Therefore, the developed learning model was proven to be valid and practical for use in PJOK learning to improve senior high school students’ Dollyo Chagi kicking skills. Keywords: Dollyo Chagi, Learning Model, Physical Education, Taekwondo